INTERNALISASI NILAI-NILAI SPIRITUAL SISWA SEKOLAH DASAR DALAM PEMBELAJARAN MATEMATIKA DENGAN STRATEGI POLYA - Salsabila Salsabila; Supriyadi Supriyadi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to analyze the effect of internalizing the spiritual values of elementary school students in learning mathematics with the polya strategy on problem solving abilities. This study uses a quantitative approach with the type of pre-experimental research and the design uses one group pretest posttest design. The population in this study were 21 grade IV students at SD Negeri Candinegoro. Samples were taken using saturated sampling with a sample of 11 people. The data collection technique used was in the form of a test and the research instrument was in the form of question sheets, namely the pretest and posttest. The results of the study were calculated using the Paired Sample Test T-test formula. Seen from sig. (two sides) significant at 0.000 < 0.05. That is, there is a significant difference from the condition of students before and after being given treatment. To find out the difference, see table 4.1. It can be seen that the post-test average is 89.29, greater than the pre-test average of 65.47. Because the average posttest is greater, the internalization of religious values in learning mathematics with a strategy can be said to have an effective effect on problem solving abilities. Keywords - Spiritual Values; Polya Strategy; Mathematical Problem Solving